Development and characteristics of the winter rye variety ‘Talovskaya 45’ - V. V. Chaikin; А. А. Torop; E. А. Torop (Зерновое хозяйство России, 2022)
There has been shown a main direction of winter rye breeding in the institution. There have been described the main stages of this process. There has been reported that the reduction in the length of the stem at the first stage due to the use of sources of short stems made it possible to increase the productivity level of the developed varieties on 17.2 %, and lodging resistance on 32.0 %. In order to compensate for the significant reduction of the assimilation surface area due to a stem length decrease as a main assimilating organ in rye, and to increase the role of leaves in this process, there have been developed the varieties with high resistance to a group of diseases, including leaf ones. In order to increase productivity and its stability, there were subsequently developed and used the large-leafy forms with an erectoid orientation. As a result, a productivity potential of the varieties reached 9 or more tons per hectare. The late-term variety ‘Talovskaya 45’ developed as a result of long-term and purposeful breeding, has been characterized as highly productive, winter tolerant, resistant to lodging and drought. The variety has been recommended for cultivation in three regions, namely Central Blackearth, Central and Middle Volga. The productivity on variety testing plots in these regions during the years of trials averaged 5.25 t/ha, 4.50 t/ha and 4.52 t/ha, respectively, and the maximum yield was 8.92 t/ha. The excess of the new variety over the standard varieties reached 0.5 or more tons per hectare. There has been given a morpho-biological characteristics of the new variety. The purpose of the current study was to show the efficiency of further improvement of the plant architectonics in improving winter rye productivity, to tell the history of development and provide a description of the new variety.